Hubungan Suhu Permukaan Laut dan Klorofil-a Dengan Hasil Tangkapan Benih Lobster di Perairan Selatan Pulau Lombok - Junaidi, Muhammad; Cokrowati, Nunik; Diniarti, Nanda; Dwi Hari Setyono, Bagus; Fitriani Mulyani, Laily (Universitas Trunojoyo Madura, 2021)
The waters south of the island of Lombok, Nusa Tenggara Province, are the location for lobster seed production. To maintain the sustainability of lobster seed resources, research is needed to know the distribution of Sea Surface Temperature (SST), chlorophyll-a and lobster seed catch and analyze the relationship between SST and chlorophyll-a on lobster seed catches. The research method used is a descriptive method that describes the state of SST and chlorophyll-a associated with the catch of seeds. Lobster seed catch data was obtained from the 2009-2013 lobster seed census, SST data and chlorophyll-a concentrations from 2009 - 2013 from the Aqua Modis satellite. The results showed that the distribution of sea surface temperature (SST) and chlorophyll-a in the Southern Waters of Lombok Island varied every season, with SST and high chlorophyll-a concentrations generally found in coastal waters and the concentration was decreasing towards the offshore direction. SPL and chlorophyll-a variables simultaneously had a significant effect on the CPUE of lobster seeds and partially SPL had no significant effect on the CPUE of lobster seeds, while chlorophyll-a had a significant effect.